(untitled) (Tarombo: Journal of Christian Theology, Education, and Ministry, 2026)
ABSTRACT National crises in Indonesia, including social conflict, political polarization, economic inequality, and moral degradation, require active involvement from various societal elements, including the church. This study aims to analyze the role of the church in responding to national crises from both theological and practical perspectives. The method used is qualitative research through a literature study approach, biblical-theological analysis, comparative theological analysis, and a conceptual-analytical framework. The findings indicate that the church plays a strategic role as an agent of social transformation through strengthening moral values, fostering social reconciliation, providing diaconal services, and delivering contextual faith education. The church functions not only as a religious institution but also as a community that brings hope, justice, and peace amid crisis situations. This study offers an integrative theological framework that connects biblical, theological, and social dimensions of the church’s role in responding to national crises. Keywords: Church, National Crisis, Social Theology, Transformation, Indonesia ABSTRAK Krisis nasional di Indonesia, termasuk konflik sosial, polarisasi politik, ketimpangan ekonomi, dan degradasi moral, menuntut keterlibatan aktif dari berbagai elemen masyarakat, termasuk gereja. Penelitian ini bertujuan untuk menganalisis peran gereja dalam merespons krisis nasional dari perspektif teologis dan praktis. Metode yang digunakan adalah penelitian kualitatif melalui pendekatan studi literatur, analisis biblika-teologis, analisis teologis komparatif, serta kerangka analisis konseptual. Hasil penelitian menunjukkan bahwa gereja memiliki peran strategis sebagai agen transformasi sosial melalui penguatan nilai-nilai moral, pembangunan rekonsiliasi sosial, penyediaan pelayanan diakonia, serta penyelenggaraan pendidikan iman yang kontekstual. Gereja berfungsi tidak hanya sebagai institusi keagamaan, tetapi juga sebagai komunitas yang menghadirkan harapan, keadilan, dan damai sejahtera di tengah situasi krisis. Penelitian ini menawarkan kerangka teologis integratif yang menghubungkan dimensi biblika, teologis, dan sosial dari peran gereja dalam merespons krisis nasional. Kata kunci: Gereja, Krisis Nasional, Teologi Sosial, Transformasi, Indonesia